Diagnostic Accuracy of the Enhanced Liver Fibrosis (ELF®) Score Using HCV-Infected Serum Samples Cryopreserved for up to 25 Years - Puigvehí, Marc; Hernández, Juanjo; Broquetas, Teresa; Coll, Susanna; Garcia-Retortillo, Montserrat; Cañete, Nuria; Giménez, Maria Dolors; Garcia, Mar; Bory, Felipe; Salvadó, Margarita; Solà, Ricard; Carrión, José A. (PLOS ONE, 2016)
Introduction & Aims Cryopreservation of serum samples is a standard procedure for biomedical research in tertiary centers. However, studies evaluating the long-term biological stability of direct liver fibrosis markers using cryopreserved samples are scarce. Methods We compared the stability of hyaluronic acid (HA), tissue inhibitor of metalloproteinases (TIMP-1) and amino-terminal propeptide of type III procollagen (PIIINP) in 225 frozen serum samples of HCV-infected patients with a paired liver biopsy for up to 25 years (1990–2014). Moreover, we assessed the diagnostic accuracy (AUROC) of the Enhanced Liver Fibrosis (ELF®) score to identify significant fibrosis (F2-4) and its predictive capacity to identify clinical events during follow-up. Results Seventy-six patients (39,8%) had mild fibrosis (F0-1) and 115 (60,2%) significant fibrosis (F2-4). HA, PIIINP and TIMP-1 values remained stable during the period from 1995 to 2014 while those of 1990–94 were slightly higher. We did not find significant differences in the median ELF® values during the 20-year period from 1995–2014 in patients with mild (from 8,4 to 8,7) and significant fibrosis (from 9,9 to 10,9) (p = ns between periods and fibrosis stages). The AUROCs of ELF® to identify significant fibrosis were high in all the periods (from 0,85 to 0,91). The ELF® score showed a good predictive capability to identify clinical events during follow-up. Conclusions The biological stability of direct serum markers (HA, PIIINP and TIMP-1) using HCV-infected samples cryopreserved for 20 years is good. Therefore, the diagnostic accuracy of the ELF® score to identify significant fibrosis and clinical events during follow-up is very high.